English Congregational Hymns in the Eighteenth Century - Marshall, Madeleine Forell, 1946- (Book collections on Project MUSE., 1982)
Historians of the English congregational hymn, focusing on its literary or theological aspects, have usually found the genre out of step with the rationalist era that produced it. This book takes a more balanced approach to the work of four writers and concludes that only eighteenth-century Britain, with its understanding of public verse, common truth, and the utility of poetry, could have invented the English hymn as we know it. The early hymns sought to inspire, teach, stir, and entertain congregations. The essential purpose shifted slightly in line with each poet's setting and in accord with.